IMPROVING STUDENT’S VOCABULARY MASTERY THROUGH EARLY HEALTH EDUCATION VIDEO AT PRADNYANDARI I KINDERGARTEN - Si Putu Agung Ayu Pertiwi Dewi; Ni Komang Purwaningsih (STKIP Persada Khatulistiwa Sintang, 2019)
This research is a classroom action research on improving English vocabulary in kindergarten students through health education video. The purpose of this study is to find out the improvement of English vocabulary through early health education video. The results of this study indicate an increase in English vocabulary through the health education video on preschool students of Pradnyandari I Kindergarten. The research method used in this research is Action research with the subject of TK Pradnyadari I Kindergarten student. Data collection techniques are using observation, documentation interviews and a collection of English words about dental and oral health through early health education video. This research was conducted in 3 cycles. The results showed an increase in vocabulary ability in English through early health education video on Pradnyandari I Kindergarten. The increase in the first cycle was 40.65%, in the second cycle, 48% and a significant increase of 65.9% was in the third cycle. It can be concluded that the increase in vocabulary through early health education videos is effectively implemented to students of Pradnyandari I Kindergarten.Keywords: English, vocabulary, health education video